Validation of a paediatric sepsis screening tool to identify children with sepsis in the emergency department: a statewide prospective cohort study in Queensland, Australia - Paula Lister; Kristen Gibbons; Luregn J Schlapbach; Adam Irwin; Michael Rice; Sainath Raman; Amanda Harley; Patricia Gilholm (BMJ Open)
Objective The Surviving Sepsis Campaign guidelines recommend the implementation of systematic screening for sepsis. We aimed to validate a paediatric sepsis screening tool and derive a simplified screening tool.Design Prospective multicentre study conducted between August 2018 and December 2019. We assessed the performance of the paediatric sepsis screening tool using stepwise multiple logistic regression analyses with 10-fold cross-validation and evaluated the final model at defined risk thresholds.Setting Twelve emergency departments (EDs) in Queensland, Australia.Participants 3473 children screened for sepsis, of which 523 (15.1%) were diagnosed with sepsis.Interventions A 32-item paediatric sepsis screening tool including rapidly available information from triage, risk factors and targeted physical examination.Primary outcome measure Senior medical officer-diagnosed sepsis combined with the administration of intravenous antibiotics in the ED.Results The 32-item paediatric sepsis screening tool had good predictive performance (area under the receiver operating characteristic curve (AUC) 0.80, 95% CI 0.78 to 0.82). A simplified tool containing 16 of 32 criteria had comparable performance and retained an AUC of 0.80 (95% CI 0.78 to 0.82). To reach a sensitivity of 90% (95% CI 87% to 92%), the final model achieved a specificity of 51% (95% CI 49% to 53%). Sensitivity analyses using the outcomes of sepsis-associated organ dysfunction (AUC 0.84, 95% CI 0.81 to 0.87) and septic shock (AUC 0.84, 95% CI 0.81 to 0.88) confirmed the main results.Conclusions A simplified paediatric sepsis screening tool performed well to identify children with sepsis in the ED. Implementation of sepsis screening tools may improve the timely recognition and treatment of sepsis.